Development and validation of a nomogram for predicting the six-year risk of cognitive impairment among Chinese older adults - Zhou, Jinhui (J Am Med Dir Assoc, 2020)
OBJECTIVE: Although some people with mild cognitive impairment may not suffer from dementia lifelong, about 5% of them will progress to dementia within one year in community settings. However, a general tool for predicting the risk of cognitive impairment was not adequately studied among older adults. DESIGN: Prospective cohort study. SETTING: Community-living, older adults from 22 provinces in China. PARTICIPANTS: We included 10,066 older adults aged 65 and above (mean age, 83.2±11.1 years), without cognitive impairment at baseline in the 2002–2008 cohort and 9354 older adults (mean age, 83.5±10.8 years) in the 2008–2014 cohort of the Chinese Longitudinal Healthy Longevity Survey. METHODS: We measured cognitive function using the Chinese version of the Mini-Mental State Examination (MMSE). Demographic, medical, and lifestyle information was used to develop the nomogram via a Lasso selection procedure using a Cox proportional hazards regression model. We validated the nomogram internally with 2000 bootstrap resamples and externally in a later cohort. The predictive accuracy and discriminative ability of the nomogram were measured by area-under-the-curves (AUCs) and calibration curves, respectively. RESULTS: Eight factors were identified with which to construct the nomogram: age, baseline MMSE, activities of daily living and instrumental activities of daily living score, chewing ability, visual function, history of stroke, watching TV or listening to the radio, and growing flowers or raising pets. The AUCs for internal and external validation were 0.891 and 0.867, respectively, for predicting incident cognitive impairment. The calibration curves showed good consistency between nomogram-based predictions and observations. CONCLUSION AND IMPLICATIONS: The nomogram-based prediction yielded consistent results in two separate large cohorts. This feasible prognostic nomogram constructed using readily ascertained information may assist public health practitioners or physicians to provide preventive interventions of cognitive impairment.